2003
DOI: 10.1023/b:neon.0000003753.27452.20
|View full text |Cite
|
Sign up to set email alerts
|

Cauda Equina Paraganglioma: A Review

Abstract: Although rare, cauda equina paraganglioma (CEP) is definitely established in the table of cauda equina tumours. There are no particular investigations to document its preoperative diagnosis, unless a vasomotor amine syndrome is present to guide the differential diagnostic spectrum. Magnetic resonance imaging is the examination of choice for the presurgical assessment, but there are still overlapping findings, mainly among CEP, ependymoma, schwannoma, and hemangioblastoma. It is also the only means for postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 79 publications
1
44
0
3
Order By: Relevance
“…[3][4][5][6][7] Surprisingly, overproduction of catecholamines occurred in only one of these five patients. 7 Despite the neuroendocrine origin of these tumours, only four patients were found to have cauda equina paraganglioma with functional hormonal activity, 2,8-10 one of which refers to my publication.…”
Section: Dear Professor Kayementioning
confidence: 89%
“…[3][4][5][6][7] Surprisingly, overproduction of catecholamines occurred in only one of these five patients. 7 Despite the neuroendocrine origin of these tumours, only four patients were found to have cauda equina paraganglioma with functional hormonal activity, 2,8-10 one of which refers to my publication.…”
Section: Dear Professor Kayementioning
confidence: 89%
“…In 1972, Lerman et al reported a ganglioneuroma-paraganglioma, using present terminology, of the filum terminale. 54 According to the literature, 33,50,62,88,93 spinal paragangliomas are found more frequently in the intradural extramedullary compartment and have a high affinity for the cauda equina or filum terminale. Less common sites include cervical and thoracic regions.…”
Section: Prevalencementioning
confidence: 99%
“…As for tumors of the cauda equina or filum terminale, the most common symptoms on presentation are lower back pain and sciatica 4,62,88,93 with a mean duration of 4 years. Sensory or motor deficits have been noticed in 35% of cases.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 2 more Smart Citations